1989
DOI: 10.1017/s0031182000060972
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the production of interferon-α/β and interferon-γ during acute toxoplasmosis

Abstract: Acute toxoplasmosis was induced in mice, and interferon (IFN) production in serum and by spleen cells was evaluated during the infection period. Interferon was characterized by acid-treatment and anti-IFN-alpha/beta neutralization. In order to verify the correlation between the unusual aspects of the IFN production and the induction of immunosuppression, splenocyte mitogen responsiveness was investigated concomitantly to IFN synthesis. The activity of Toxoplasma-induced serum IFN-alpha/beta increased gradually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…IFN-α and IFN-β are predominantly produced by leucocytes and fibroblasts, respectively, although other cell types may also contribute. The increased amounts of IFN-α/β in sera from T. gondii-infected mice correlate with a reduced IFN-γ production and proliferation of splenocytes (Table 1; Diez et al 1989). This suggests that the production of IFN-α/β induced by T. gondii during acute infection is associated with parasite-induced immunosuppression.…”
Section: Modulation Of Cytokine Secretion Following T Gondii Infectionmentioning
confidence: 98%
See 2 more Smart Citations
“…IFN-α and IFN-β are predominantly produced by leucocytes and fibroblasts, respectively, although other cell types may also contribute. The increased amounts of IFN-α/β in sera from T. gondii-infected mice correlate with a reduced IFN-γ production and proliferation of splenocytes (Table 1; Diez et al 1989). This suggests that the production of IFN-α/β induced by T. gondii during acute infection is associated with parasite-induced immunosuppression.…”
Section: Modulation Of Cytokine Secretion Following T Gondii Infectionmentioning
confidence: 98%
“…These results provide clear evidence that IL-10-induced immunosuppression following infection with T. gondii is beneficial for both the parasite and the host and favours a stable parasite-host relationship. In addition to IL-10, TGF-β is an important deactivator of macrophages (Langermans et al 2001), the Khan et al 1995;Ellis Neyer et al 1997;Bermudez et al 1993;Langermans et al 2001;Hunter et al 1995 Deactivation of macrophages Independent of PGE2 Indirect Induction of TGF-β Reduced TNF-α production by macrophages; reduced IFN-γ production by NK cells Antagonizes IL-12 Indirect IFN-α/-β upregulation Reduced IFN-γ levels and splenocyte proliferation ND Indirect Diez et al 1989 Inhibition of TNF-α and IL-12 production ND not determined production of which is triggered after infection with T. gondii (Table 1; Bermudez et al 1993). It also inhibits the production of IFN-γ by NK cells (Hunter et al 1995) and may thus downregulate regulatory and effector functions of anti-Toxoplasma cellular immunity during acute toxoplasmosis (Table 1).…”
Section: Modulation Of Cytokine Secretion Following T Gondii Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mouse model, IFN-I can already be detected in the serum of T. gondii -infected animals during the acute phase (5860); IFN-I levels gradually increase with the progression of the infection (60). IFN-I was also detected in the brain and spleen of infected mice (61).…”
Section: Protozoan Parasites and Ifn-imentioning
confidence: 99%
“…As will be described below, with the use of MAB against IFN-7, Nathan et al (18) there was production of only low levels of IFN-7 which may be a manifestation of the immunosuppression present during acute toxoplasma infection (56). Furthermore, Diez et al (57) demonstrated that when normal mice were acutely infected with the RH strain of Toxoptasma gondii, as the disease progressed, there was a decline in production of IFN-7, a progressive decrease in the proliferative response of lymphocytes to mitogen and an increase in production of IFN-~13. They postulated that the production of IFN-~]3 might be an important factor associated with the immunosuppression seen in acute toxoplasma infection.…”
Section: Production Of Gamma Interferon By T Lymphocytesmentioning
confidence: 99%